Expansion of the public sector, the current account and the exchange rate - Renate Ohr (Intereconomics, 1985)
Attributing the foreign trade effects of an expansion in the state budget to a single cause cannot do justice to the multitude of macro-economic interrelationships. Both theory and observation can reveal quite differing links between the public sector financial balance, the balance of payments and the exchange rate. The financing and nature of additional budgetary expenditure and the pattern of private investors' expectations therefore have to be taken into consideration to obtain a clear picture of the possible consequences of budgetary expansion.
Keywords: 330